2011
DOI: 10.5194/acp-11-12663-2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the role of sulfuric acid in the mechanisms of new particle formation for Beijing case

Abstract: Abstract. New particle formation (NPF) is considered as an important mechanism for gas-to-particle transformation, and gaseous sulfuric acid is believed as a crucial precursor. Up to now few field-based studies on nucleation mechanisms and the role of sulfuric acid were conducted in China. In this study, simultaneously measurements of particle number size distributions and gaseous sulfuric acid concentrations were performed from July to September in 2008. Totally, 22 new particle formation events were observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 45 publications
10
67
1
4
Order By: Relevance
“…The detailed ion chemistry to generate nitrate ions and the calibration procedure for sulfuric acid measurement have been reported in Zheng et al (2015b). Ambient sulfuric acid concentration in Beijing has been reported only once in a field campaign conducted in 2008 Wang et al, 2011). Compared to that campaign, the sulfuric acid concentration measured in this study displayed similar diurnal variations, but with lower daily-maximum values.…”
Section: Methodssupporting
confidence: 51%
“…The detailed ion chemistry to generate nitrate ions and the calibration procedure for sulfuric acid measurement have been reported in Zheng et al (2015b). Ambient sulfuric acid concentration in Beijing has been reported only once in a field campaign conducted in 2008 Wang et al, 2011). Compared to that campaign, the sulfuric acid concentration measured in this study displayed similar diurnal variations, but with lower daily-maximum values.…”
Section: Methodssupporting
confidence: 51%
“…A and K refer to the activation and kinetic nucleation coefficients, respectively, with values of 3.0 × 10 −6 s −1 and 8.0 × 10 −13 cm 3 s −1 . These values are close to the measured median values of 17 NPF event days during CAREBeijing 2008 (Wang et al, 2013b), however, several times higher compared to the results derived from other field measurements and model simulations in clean environments (Boy et al, 2008a;Paasonen et al, 2010;Riipinen et al, 2007;Wang et al, 2011). Recent research results indicate that sulfuric acid is not the only compound taking part in new particle formation, but low-volatile organic vapours are also needed Lauros et al, 2011;Metzger et al, 2010;Riipinen et al, 2012).…”
Section: Aerosolsupporting
confidence: 49%
“…The upper bound, d u , is selected as 6 nm is some recent studies (Sihto et al, 2006;Riipinen et al, 2007;Paasonen et al, 2009;Wang et al, 2011;Vuollekoski et al, 2012; as shown in Eq. (8).…”
Section: Previous Formulae For Comparisonmentioning
confidence: 99%
“…Kulmala et al (2004) recommended the upper size bound as the maximum size that the critical cluster can reach during a short time interval of growth. There are also studies using narrower size ranges, such as from 3 to 6 nm (Sihto et al, 2006;Paasonen et al, 2009;Wang et al, 2011;Vuollekoski et al, 2012) and from 1.34 to 3 nm (Xiao et al, 2015). In principle, the estimated formation rates may vary when different particle size ranges are used.…”
Section: Introductionmentioning
confidence: 99%